The relationship between attachment and offending within a South African context - Barber, Megan (Department of Psychology, 2018)
International research has consistently documented a link between attachment and offending. Despite South Africa's high crime rate, research within this country's socio-political context has been limited. This current study aimed to fill this gap, by examining the association between attachment and offending within a South African context. It was hypothesised that: H1, an insecure attachment would occur more frequently in offenders than non-offenders; H2, high attachment-related avoidance would be positively associated with offending; H3, high attachment-related avoidance would be positively associated with antisocial behaviour; and H4, an insecure mother attachment would be more strongly associated with offending than an insecure father or intimate partner attachment. Two groups of participants were recruited: offenders (n = 49) and a community sample (n = 63). Each participant completed a questionnaire measuring attachment to mothers, fathers, and intimate partners, as well as socio-economic status and antisocial behaviour. Using a series of statistical tests including chi-square, logistic regression, and hierarchical multiple regression, the study found support for H1 and H2, whilst rejecting H3 and H4. Overall, this study found that insecure attachment, and specifically high attachment-related avoidance, was positively associated with offending. Conversely, it was found that low avoidance was associated with antisocial behaviour and that there was no association between specific domains (mother, father and intimate partner) of attachment and offending. These results provide support for the application of attachment theory to offenders within the South African context.